Do Recovery Loan, Physical Fund, And Social Grant Affect Gross Regional Products? - Deni Herdiyana; Irfan Sofi; Sutarto Sutarto; Hari Sugiyanto (Politeknik Keuangan Negara STAN, 2023)
Research objective: This research aims to investigate the impact of economic recovery loans (PEN), physical allocation funds (DAK), and social grant of village fund (BLT) on the gross domestic regional product (GDRP) of Indonesian districts and cities through unbalanced data panel regression. Method: This research was conducted using the quantitative method using documentation for collecting the numerical data and panel regression for analyzing the data. Research findings: The research finds that each of PEN, DAK, or BLT has a positive and significant influence on GDRP. Moreover, the implementation of the BLT has been very effective, even though, there are several obstacles, including budget limitations, mismatch in recipient data, and lack of distribution facilities. Practical implication: This study suggests that PEN should be continued to accelerate economic recovery for regions affected by COVID-19, but the selection of regional governments as beneficiaries should be more selective.